2016
DOI: 10.15376/biores.11.1.2712-2722
|View full text |Cite
|
Sign up to set email alerts
|

Development of Improved Process with Treatment of Cellulase for Isolation of Ampelopsin from Dried Fruits of Ampelopsis grossedentata

Abstract: The commercial method for isolation of ampelopsin, one of the most common flavonoids isolated from the plant species Ampelopsis grossedentata, is a simple hydrothermal extraction at high temperature. To develop an improved process to isolate ampelopsin, the effects of treatment of cellulase on hydrolysis of the dried fruit of A. grossedentata were investigated. The treatment of cellulase was found to decrease the temperature and time for hydrolysis of the dried fruit of A. grossedentata. The conditions of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
(35 reference statements)
0
8
0
Order By: Relevance
“…Dihydromyricetin (3,5,7,3 ′ ,4 ′ ,5 ′ -hexahydroxy-2,3-dihydroflavonol (DHM)) ( Figure 1), also known as ampelopsin, is a major flavonoid extracted from the leaves and stems of A. grossedentata. The content of DHM in A. grossedentata ranges from 30% to 40% (dry weight), which is considered to have the highest flavonoid content in natural plants [1]. Several scientific investigations reported that DHM possesses various biological activities such as anti-inflammatory [2,3], antioxidative [4,5], anticancer [6,7], antidiabetic [8][9][10], antiatherosclerosis [11,12], and cardioprotective effects [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Dihydromyricetin (3,5,7,3 ′ ,4 ′ ,5 ′ -hexahydroxy-2,3-dihydroflavonol (DHM)) ( Figure 1), also known as ampelopsin, is a major flavonoid extracted from the leaves and stems of A. grossedentata. The content of DHM in A. grossedentata ranges from 30% to 40% (dry weight), which is considered to have the highest flavonoid content in natural plants [1]. Several scientific investigations reported that DHM possesses various biological activities such as anti-inflammatory [2,3], antioxidative [4,5], anticancer [6,7], antidiabetic [8][9][10], antiatherosclerosis [11,12], and cardioprotective effects [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…DMY was first isolated from Ampelopsis meliaefolia by Kotake and Kubota in 1940, and was later reported as a major bioactive component in A. grossedentata (Zhang, Yang, & Xiong, 2001;Kou & Chen, 2012). The content of DMY was as high as 30-40% (w/w) in A. grossedentata (Tian, Zhang, Yang, Yang, & Gong, 2002;Gao, Lee, Li, & Lee, 2016). Other major sources of DMY also include medical plants such as Hovenia dulcis (Yoo, Mun, & Kim, 2006;Chaturvedula & Ruo, 2013) and Cedrus deodara (Liang, Shen, et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Cellulase is one of the common used hydrolytic enzymes to hydrolyze and decompose the components of cell wall and enhance the release of intracellular constituents (Fu et al, 2008). Furthermore, cellulase has been proved to be efficient for the extraction of flavonoids from different kinds of plant materials including Illicium verum (Huang et al, 2016), Ampelopsis grossedentata (Gao et al, 2016), Larix gmelini (Wang et al, 2011) and Geranium sibiricum L. (Yang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%